Connecting Knowledge Creation, Management, and Transfer Organizations into the Innovation Startup Ecosystem: Models and Policies - Huy Nhuong, Bui (VNU Journal of Science: Policy and Management Studies; Vol 41 No 3, 2025)
This article proposes a multi-actor connectivity model for organizations involved in knowledge creation, management, and transfer (including research and development, technology transfer, intellectual property, and innovation organizations) within Vietnam’s innovation startup ecosystem. The model is grounded in open ecosystem theory and built upon surveys at over 20 organizations, three national workshops organized by the research team (2023-2024), and international experience. Structured across three levels-institutions, connection platforms, and implementation tools, it aims to address fragmentation and foster an integrated, sustainable, and globally connected ecosystem.